2022
DOI: 10.3390/challe13010018
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of Silver Nanoparticles from Cymbopogon citratus Leaf Extract and Evaluation of Their Antimicrobial Properties

Abstract: Background: Silver nanoparticles (AgNPs) are toxic to microorganisms and can potentially kill multidrug-resistant bacteria. Nanoparticles can be synthesized in many ways, such as physical or chemical methods. Recently, it has been found that plant molecules can perform the same reduction reactions necessary for the production of nanoparticles but in a much more efficient way. Results: Here, green chemistry was employed to synthesize AgNPs using leaf extracts of Cymbopogon citratus. The effects of different par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 55 publications
5
24
0
Order By: Relevance
“…AgNPs synthesis by means of green methods represents the focus of scientists, given that they imply lower costs and ease in the monitoring and sampling processes. Moreover, plants are easy to grow and safe to handle, and, implicitly, this type of eco-friendly synthesis could replace chemical techniques for obtaining AgNPs [ 29 ]. The steps implied by AgNPs synthesis are represented by the reduction of Ag + and agglomeration of colloidal nanoparticles with oligomeric clusters formation [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…AgNPs synthesis by means of green methods represents the focus of scientists, given that they imply lower costs and ease in the monitoring and sampling processes. Moreover, plants are easy to grow and safe to handle, and, implicitly, this type of eco-friendly synthesis could replace chemical techniques for obtaining AgNPs [ 29 ]. The steps implied by AgNPs synthesis are represented by the reduction of Ag + and agglomeration of colloidal nanoparticles with oligomeric clusters formation [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…When analyzing the UV-Vis spectra, no absorption peak was observed in the 300–600 range for either the extract or AgNO 3 solution, but a distinct peak at 410 nm was revealed for the obtained colloidal solution. This peak could be due to excitation of SPR [ 31 ], which could determine the optical, physical and chemical properties of AgNPs [ 29 ]. The presence of a single SPR peak could explain the spherical shape of AgNPs [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to their unique optical, magnetic, electronic, and chemical properties and capacity for multiplexing, nanoparticles have been useful in diagnostics, drug delivery and biomedical imaging. [1][2][3] NPs have also been used to advance tissue engineering, regenerative medicine, and stem cell biology by developing an effective cell/tissue-biomaterial interface to support biological functions. 1,4,5 In particular, particles with both magnetic and electric properties have attracted specific interest because of the tremendous potential for targeted drug delivery and control of biological functions.…”
Section: Introductionmentioning
confidence: 99%
“…14 Plant-mediated synthesis provides major benefits, including its ease of monitoring, low time consumption, low cost, and effective replacement of chemicals in the reduction process, and is the safest choice to produce silver nanoparticles. 5,15,16 Recent studies have reported that parts of the plant used for biosynthesized silver nanoparticles are roots, 17 leaves, [18][19][20] seeds 21,22 and bark. 23 Plant extracts contain many bioactive compounds (e.g.…”
Section: Introductionmentioning
confidence: 99%